GD1b-Derived Gangliosides Modulate FcεRI Endocytosis in Mast Cells - Mazucato, Vivian Marino (SAGE Publications, 2011)
The role of the mast cell–specific gangliosides in the modulation of the endocytic pathway of FcεRI was investigated in RBL-2H3 cells and in the ganglioside-deficient cell lines, E5 and D1. MAb BC4, which binds to the α subunit of FcεRI, was used in the analysis of receptor internalization. After incubation with BC4-FITC for 30 min, endocytic vesicles in RBL-2H3 and E5 cells were dispersed in the cytoplasm. After 1 hr, the endocytic vesicles of the RBL-2H3 cells had fused and formed clusters, whereas in the E5 cells, the fusion was slower. In contrast, in D1 cells, the endocytic vesicles were smaller and remained close to the plasma membrane even after 3 hr of incubation. When incubated with BC4-FITC and subsequently imunolabeled for markers of various endocytic compartments, a defect in the endocytic pathway in the E5 and D1 cells became evident. In the D1 cells, this defect was observed at the initial steps of endocytosis. Therefore, the ganglioside derivatives from GD1b are important in the endocytosis of FcεRI in mast cells. Because gangliosides may play a role in mast cell–related disease processes, they provide an attractive target for drug therapy and diagnosis.